2015
DOI: 10.1088/2041-8205/802/2/l14
|View full text |Cite
|
Sign up to set email alerts
|

Sofia/Exes Observations of Water Absorption in the Protostar Afgl 2591 at High Spectral Resolution

Abstract: We present high spectral resolution (∼3 km s −1 ) observations of the n 2 ro-vibrational band of H 2 O in the 6.086-6.135 μm range toward the massive protostar AFGL 2591 using the Echelon-Cross-Echelle Spectrograph (EXES) on the Stratospheric Observatory for Infrared Astronomy (SOFIA). Ten absorption features are detected in total, with seven caused by transitions in the n 2 band of H 2 O, two by transitions in the first vibrationally excited n 2 band of H 2 O, and one by a transition in the n 2 band of H 2 18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
(69 reference statements)
3
22
0
Order By: Relevance
“…This number is consistent with the measured gaseous H 2 O column densities relative to those of hot H 2 in the inner region (Boonman & van Dishoeck 2003), with H 2 derived from CO infrared absorption lines obtained with the CFHT-FTS by Mitchell et al (1990) assuming CO/H 2 = 2 × 10 −4 . Interestingly, the corresponding ratio H 2 O/CO≈0.6 is similar to that found by Indriolo et al (2015a) for some of the same lines of sight using much higher spectral resolution H 2 O data obtained with SOFIA-EXES and VLT-CRIRES. Assuming that atomic O and O 2 are negligible, this gives a total of 162 ppm accounted for in the gas.…”
Section: G32 High-mass Protostarssupporting
confidence: 84%
See 1 more Smart Citation
“…This number is consistent with the measured gaseous H 2 O column densities relative to those of hot H 2 in the inner region (Boonman & van Dishoeck 2003), with H 2 derived from CO infrared absorption lines obtained with the CFHT-FTS by Mitchell et al (1990) assuming CO/H 2 = 2 × 10 −4 . Interestingly, the corresponding ratio H 2 O/CO≈0.6 is similar to that found by Indriolo et al (2015a) for some of the same lines of sight using much higher spectral resolution H 2 O data obtained with SOFIA-EXES and VLT-CRIRES. Assuming that atomic O and O 2 are negligible, this gives a total of 162 ppm accounted for in the gas.…”
Section: G32 High-mass Protostarssupporting
confidence: 84%
“…Independent evidence that H 2 O does not contain all of the oxygen comes from mid-infrared absorption line observations with ISO and SOFIA of hot water and CO along the lines of sight to massive protostars, many of them the same sources as included in the WISH sample Boonman & van Dishoeck 2003). In particular, high spectral resolution absorption line observations at 6 µm using SOFIA-EXES give N(H 2 O)/N(CO) ≈ 0.7 for gas at ∼1000 K, a factor of 2-3 less than expected if all oxygen is in water (Indriolo et al 2015a).…”
Section: Outflow Positionsmentioning
confidence: 97%
“…Our analysis is focused on the hot core AFGL 2591 VLA 3 whose kinematic and chemical properties have been studied at multiple wavelengths in the past. Based on the kinematic properties using PdBI observations of HDO, H 18 2 O, and SO 2 , Wang et al (2012) found a Hubble law-like expansion within the inner 2400 au, and argue that this is caused by a disk wind, (Indriolo et al 2015;Barr et al 2018). Jiménez-Serra et al (2012) reported chemical segregation on scales smaller than 3000 au due to the interplay between molecular dissociation by UV radiation, ice evaporation, and high-temperature gas-phase chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…They detected CS in absorption, however only 6 lines were observed, as well as HNCO and CH 3 for the first time in the IR. Indriolo et al (2015) studied H 2 O absorption towards AFGL 2591 with the Echelon-Cross-Echelle Spectrograph (EXES; Richter et al 2010).…”
Section: Introductionmentioning
confidence: 99%